Wilt Thou Be Lord of all the World? Modals and Persuasion in Shakespeare - Nakayasu, Minako (Studia Anglica Posnaniensia, 2014)
This research thus clarifies how effectively speakers attempted to persuade others in interactions, shedding light on communication mechanisms in the past.